Eksploitasi Kredibilitas Profesi dalam Pemasaran dan Pelanggaran Etika Bisnis pada Produk Skincare - Maryo Putra Rahayu; Halimah Zahrah; Annisa Zaida Rahman; Siti Kamila Nurhasanah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The development of the skincare industry in Indonesia has encouraged the emergence of various marketing strategies that often ignore the principles of business and professional ethics. This research examines the practice of exploiting the credibility of the medical profession in the promotion of Athena skincare products, which is carried out by an influencer doctor. This study uses forms of ethical violations in the case of overclaiming the content of White Tomato and Salmon DNA, the practice of repackaging imported products without re-notification to BPOM, and the use of microneedle application methods that contradict the definition of cosmetics. The findings show that the involvement of medical personnel in commercial promotion without clear scientific basis violates the principles of honesty, social responsibility, and professional integrity as stipulated in the Indonesian Medical Code of Ethics and business ethics theory. Such violations negatively impact public trust, create public disinformation, and pose risks to consumer health. This research emphasizes the importance of post-approval cosmetic regulation reform, strengthening professional code of ethics in the digital era, and consumer literacy as strategic steps to build a more ethical and responsible skincare industry.